Edukasi tentang Teknik Pijat untuk Mengurangi Nyeri Haid - Sri Wulan Ratna Dewi; Sandriani (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: The impact of menstrual pain on adolescent girls includes: disturbed comfort, decreased activity, disturbed sleep patterns, disturbed appetite, relationships Interpersonal problems, difficulty concentrating on work and study. Pain too affect the emotional status of feelings, irritability, depression and anxiety. The earliest changes that occur in adolescents are physical or biological development, one of them is a teenager starting to menstruate. Objective: students can use massage techniques to reduce menstrual pain when menstrual pain occurs. Method: The implementation method is by counseling. This community service activity starts with (1) preparation; This stage begins with a preliminary study that aims to explore the problem of menstrual pain in Diploma Midwifery study program students, determine target activities, and plan solutions to problems. Next, they asked permission from the Head of the Diploma Midwifery Study Program to conduct outreach to students, (2) implementation. The activities are adjusted to the student mentoring schedule, (3) reporting, at this stage the team reports the results of the activities that have been carried out to the Head of Diploma Midwifery Study Program. Result: the results of community service found that after attending counseling on massage techniques for reducing menstrual pain, students were able to apply techniques that were late in practice, although some massage techniques had to be assisted by others. After students know about massage  techniques to reduce menstrual pain, some students rarely experience menstrual pain during menstruation. Conclusion: from the results of community service about massage techniques to reduce menstrual pain, it can be concluded that there is a decrease in menstrual pain after massage techniques are carried out to reduce menstrual pain.